Food preference and the effect of predator cues on the foraging behaviour of House Rat (Rattus tanezumi) - Wong, Lok Jinn; Alek, Andrew Tuen (Penerbit Universiti Kebangsaan Malaysia, 2020)
The House Rat (Rattus tanezumi) is a major pest in the agriculture and food industry, a carrier of zoonotic diseases, and a source of nuisance to society. Poisoning is not an ecologically desirable method to control the rat population due to its effect on non-target animals. This article reported on the use of predator cues to control the rat’s foraging behavior. Food preference for sugarcane, corn, oil palm fruit, and young coconut flesh was determined first using a modified “cafeteria method” with a central cage connected to four feeding stations by PVC tubes. Then the effect of predator cues (3-D model and call of an owl, a combination of model and call and no predator cue as control) on foraging behavior was tested by manipulating these cues near the feeding station. Giving up density (GUD), which is the amount of food remaining at the feeding stations, was measured in both experimental phases. Treatment means were analyzed using ANOVA and compared using the Tukey test. The finding showed that House Rats preferred young coconut flesh over other test foods. All predator cues increased GUD significantly (p<0.01) but the 3-D model was the most effective. This study suggests a potential use of predator cues to control rat pest.